PENERAPAN MODEL DISCOVERY LEARNING PADA PEMBELAJARAN DARING MATERI HIMPUNAN SISWA KELAS VII - Tari Mulyani; M. Afrilianto; Dini Rosdiani (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
In this study using classroom action research.  The goal is to find out information on the application of the discovery learning  model to online learning of set materials to improve the learning outcomes of junior high school students. With the implementation of research on class VII-E students at one state junior high school in Cimahi City, totaling 37 people. This class action research is carried out in 2 cycles, where each cycle has 2 meetings. The research instrument uses observations, study test results, and journals conducted online. Analyze the data in the form of average and percentage results with descriptive statistics. The average score of 71.64 with a percentage of 56.75% is the learning outcome of students in the first cycle and the average score of 80.74 with a percentage of 86.48% is the learning outcome of students in cycle II. The activities of teachers and students in each cycle in online learning are quite good and effective but there is something that needs to be improved in student activity during the online learning process. It is concluded that there is an increase in student learning outcomes in online learning, so the discovery learning  model can be applied to class VII students of the set material.